Syndromic Deafness Gene ATP6V1B2 Controls Degeneration of Spiral Ganglion Neurons Through Modulating Proton Flux - Qiu, Shiwei; Zhao, Weihao; Gao, Xue; Li, Dapeng; Wang, Weiqian; Gao, Bo; Han, Weiju; Yang, Shiming; Dai, Pu; Cao, Peng; Yuan, Yongyi (Frontiers in Cell and Developmental Biology, 2021)
ATP6V1B2 encodes the V1B2 subunit in V-ATPase, a proton pumpresponsible for the acidification of lysosomes. Mutations in this gene cause DDOD syndrome, DOORS syndrome, and Zimmermann-Laband syndrome, which share overlapping feature of congenital sensorineural deafness, onychodystrophy, and different extents of intellectual disability without or with epilepsy. However, the underlying mechanismis unclear.To investigate the pathological role of mutant ATP6V1B2 in the auditory system, we evaluated auditory brainstem response, distortion product otoacoustic emissions, in a transgenic line of mice carrying c.1516 C>T (p.Arg506*) in Atp6v1b2, Atp6v1b2Arg506*/Arg506*. To explore the pathogenic mechanism of neurodegeneration in the auditory pathway, immunostaining, western blotting, and RNAscope analyses were performed in Atp6v1b2Arg506*/Arg506* mice. The Atp6v1b2Arg506*/Arg506* mice showed hidden hearing loss at early stages and developed late-onset hearing loss. We observed increased transcription of Atp6v1b1 inhair cellsof Atp6v1b2Arg506*/Arg506* mice and inferred that Atp6v1b1 compensated for the Atp6v1b2 dysfunction by increasing its own transcription level. Genetic compensation in hair cells explains the milder hearing impairment in Atp6v1b2Arg506*/Arg506* mice.Apoptosis activated by lysosomal dysfunction and the subsequent blockade of autophagic flux induced the degeneration of spiral ganglion neurons and further impaired the hearing.Intraperitoneal administration ofthe apoptosis inhibitor, BIP-V5, improved bothphenotypical and pathological outcomes in two live mutant mice.Based on the pathogenesis underlying hearing loss in ATP6V1B2-related syndromes,systemic drug administration to inhibit apoptosis might be an option for restoring the function of spiral ganglion neurons and promoting hearing, which provides a direction for future treatment.